Implementasi Konsep Age-Friendly City dalam Menghadapi Tantangan Demografi Lansia di Kota Yogyakarta: indonesia - Hidayat, Ridhan; Murtanti Jani Rahayu; Hakimatul Mukaromah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The increasing number of elderly people in Yogyakarta City demands the provision of an inclusive environment that supports the welfare of the elderly. This study aims to assess the suitability of Yogyakarta City for the concept of an elderly-friendly city based on seven main variables: green open space, public transportation, pedestrian facilities, health services, social support, elderly-friendly intergenerational interactions, and advocacy for the basic rights of the elderly. The research used a quantitative approach with observation and questionnaire methods to elderly people in all sub-districts in Yogyakarta City. The data were analyzed using a Guttman scale to determine the level of suitability of each variable. The results showed that overall Yogyakarta City is classified as “suitable” for the concept of an elderly-friendly city, with a total score of 5.32 out of a maximum scale of 6.80. Four variables meet the suitability criteria, namely public transportation, health services, social support, and intergenerational interaction. Meanwhile, the other three variables are still not fully suitable and require improvement. This study recommends improvements in these three aspects so that the implementation of the concept of an elderly-friendly city in Yogyakarta City can be more optimal and sustainable.